1978
DOI: 10.1098/rstb.1978.0053
|View full text |Cite
|
Sign up to set email alerts
|

Forty-five years of change on low wooded islands, Great Barrier Reef

Abstract: During the 1928-29 Expedition, centred at Low Isles, Spender mapped the ‘low wooded islands’ or ‘island-reefs’ of Low Isles and Three Isles in detail, and additional information was published by Steers, T. A. Stephenson and others. From this work, two different models of the evolution of low wooded islands were proposed, Spender holding that the islands were in a state of equilibrium resulting from their location on the reef, Steers that they could be placed in an evolutionary sequence. Moorhouse described the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…1 : 6000 ( Figure 2) from 1928 (photo mosaic, GBRE), 1945 (oblique photographs. Royal Australian Air Force for FAIR-BRIDGE and TEICHERT, 1947TEICHERT, , 1948TEICHERT, ), 1982TEICHERT, , 1991TEICHERT, , 1996TEICHERT, , and 2001 (Australian Beach Protection Authority); (2) 1: 5000-scale maps of the Low Isles Reef surface IFAIKBRIDGE and TEICHERT, 1947;MOORHOUSE, 1936;SPENDER, 1930;STOD-DART et al, 1978); and (3} surface photographs and other data provided in reports (BELL and ELMETRI, 1995;FAIRBRIDGE andTEICHERT, 1947, 1948;GBRE, 1928-29;MOORHOUSE, 1933MOORHOUSE, , 1936STEPHENSON, ENDEAN, and BENNETF, 1958;STODDART et al, 1978;YONGE, 1930). Historical cyclone data for the area (Table 1) are compiled from the Australian Bureau of Meteorology (ABOM) and historical accounts for Low Isles Reef (MOORHOUSE, 1936;STEPHENSON, ENDEAN, and BENNETT, 1958).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…1 : 6000 ( Figure 2) from 1928 (photo mosaic, GBRE), 1945 (oblique photographs. Royal Australian Air Force for FAIR-BRIDGE and TEICHERT, 1947TEICHERT, , 1948TEICHERT, ), 1982TEICHERT, , 1991TEICHERT, , 1996TEICHERT, , and 2001 (Australian Beach Protection Authority); (2) 1: 5000-scale maps of the Low Isles Reef surface IFAIKBRIDGE and TEICHERT, 1947;MOORHOUSE, 1936;SPENDER, 1930;STOD-DART et al, 1978); and (3} surface photographs and other data provided in reports (BELL and ELMETRI, 1995;FAIRBRIDGE andTEICHERT, 1947, 1948;GBRE, 1928-29;MOORHOUSE, 1933MOORHOUSE, , 1936STEPHENSON, ENDEAN, and BENNETF, 1958;STODDART et al, 1978;YONGE, 1930). Historical cyclone data for the area (Table 1) are compiled from the Australian Bureau of Meteorology (ABOM) and historical accounts for Low Isles Reef (MOORHOUSE, 1936;STEPHENSON, ENDEAN, and BENNETT, 1958).…”
Section: Methodsmentioning
confidence: 97%
“…As noted hy STODDART et al (1978), the pattern of expansion in the area originally mapped as the mangrove park corresponds to subtle variations in reef flat topography. Much of the mangrove park area lays an average of 1.2-1.5 m above datum, somewhat higher than the remainder of the reef flat (SPENDER, 1930).…”
Section: Mangrove Swamp Expansionmentioning
confidence: 97%
“…At inter-annual to decadal timescales studies have also identified changes in island size and position on reefs (Taylor, 1924;Stoddart et al, 1978;Flood, 1986;Aston, 1995). Umbgrove (1947) and Verstappen (1954) were the first to develop a causal relationship between climate and reef island behaviour invoking medium-term (decadal) shifts in prevailing wind direction and strength and its influence on wave energy as a control on morphological adjustment of islands in Djakarta Bay, Indonesia.…”
Section: Introductionmentioning
confidence: 97%
“…They are morphologically sensitive to changes in boundary conditions (sea level, waves and currents) at a range of timescales. For example, reef islands are considered prone to widespread destruction in response to future sea-level rise (Dickinson, 1999;Kahn et al, 2002), and have been shown to morphologically adjust to climate variations at interdecadal (Taylor, 1924;Umbgrove, 1947;Verstappen, 1954;Stoddart et al, 1978;Flood, 1986) and seasonal timescales (Hopley, 1981;Kench and Brander, 2006). Extreme natural events can also alter reef island geomorphology and the character and distribution of sediments.…”
mentioning
confidence: 97%